2012
DOI: 10.1155/2012/163106
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Extract Ameliorates Learning and Memory Deficits in Ischemic Rats via Its Active Component Polyphenol Epigallocatechin-3-gallate by Modulation of Oxidative Stress and Neuroinflammation

Abstract: Ischemic stroke results in brain damage and behavioral deficits including memory impairment. Protective effects of green tea extract (GTex) and its major functional polyphenol (−)-epigallocatechin gallate (EGCG) on memory were examined in cerebral ischemic rats. GTex and EGCG were administered 1 hr before middle cerebral artery ligation in rats. GTex, EGCG, and pentoxifylline (PTX) significantly improved ishemic-induced memory impairment in a Morris water maze test. Malondialdehyde (MDA) levels, glutathione (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 58 publications
2
66
1
5
Order By: Relevance
“…This set of data shows that GT attenuates neuromotor deficit induced by hemorrhagic stroke, as previously demonstrated with ischemic stroke. It has been previously shown that GT extract and EGCG administration (the major component of green tea) attenuate neuromotor deficit, oxidative stress and lesion volume in an experimental model of focal and global ischemia (Wu et al, 2012;Chang et al, 2014;Shah et al, 2010). Chang et al (2014) had previously studied the effect of Epicatechin (EC) on a model of hemorrhagic stroke and shown that EC induces the activation of Nrf2 and protects against oxidative stress, neuromotor deficit and lesion volume in mice (Chang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This set of data shows that GT attenuates neuromotor deficit induced by hemorrhagic stroke, as previously demonstrated with ischemic stroke. It has been previously shown that GT extract and EGCG administration (the major component of green tea) attenuate neuromotor deficit, oxidative stress and lesion volume in an experimental model of focal and global ischemia (Wu et al, 2012;Chang et al, 2014;Shah et al, 2010). Chang et al (2014) had previously studied the effect of Epicatechin (EC) on a model of hemorrhagic stroke and shown that EC induces the activation of Nrf2 and protects against oxidative stress, neuromotor deficit and lesion volume in mice (Chang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Green tea (Camellia sinensis) has been reckoned as a possible source of antioxidants available through diet (Wu et al, 2012;Xu et al, 2010). Catechins, a group of flavonoids, constitute around 30-45% of the solid GT extract (reviewed in (Mak, 2012)).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Malondialdehyde (MDA), glutathione (GSH), and SOD were determined as extensively described by Wu et al (44). Kidney tissue was homogenized in 0.1 M phosphate buffer (pH 7.4) using a Ultra Turrax-T18-basic homogenizer (IKA Works, Wilmington, NC), and the homogenate was centrifuged at a 10,000 g at 4°C for 15 min to remove cellular debris.…”
Section: General Analysis Methodsmentioning
confidence: 99%
“…Biophenols are reported to affect various body systems, modulate immunity and fight pathogens and neoplasms [13]. Further, biophenols are proclaimed to affect mood, behaviour, memory and cognition [31][32][33][34][35]. Biophenols demonstrated-at least in vitro-abilities to modulate cell signalling pathways, react with specific receptors, interfere with cell division, modulate enzyme activities, regulate gene expression and affect epigenetics [13].…”
Section: What Is the Consensus?mentioning
confidence: 99%